1995
DOI: 10.1073/pnas.92.6.1941
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium-protoporphyrin chelatase of Rhodobacter sphaeroides: reconstitution of activity by combining the products of the bchH, -I, and -D genes expressed in Escherichia coli.

Abstract: Magnesium-protoporphyrin chelatase lies at the branch point of the heme and (bacterio)chlorophyll biosynthetic pathways. In this work, the photosynthetic bacterium Rhodobacter sphaeroides has been used as a model system for the study of this reaction. The Photosynthetic organisms synthesize both chlorophyll and heme, the two major tetrapyrroles in nature. The biosynthetic pathways of these two porphyrins utilize a number of intermediates in common and the first step unique to chlorophyll production is the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
166
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 183 publications
(169 citation statements)
references
References 31 publications
3
166
0
Order By: Relevance
“…Gibson et al confirmed this assignment biochemically, by cloning these genes into expression vectors [4]. The expressed proteins were all soluble, and when combined had Mg-chelatase activity.…”
Section: Mg-chelatase Has Three Componentsmentioning
confidence: 89%
See 4 more Smart Citations
“…Gibson et al confirmed this assignment biochemically, by cloning these genes into expression vectors [4]. The expressed proteins were all soluble, and when combined had Mg-chelatase activity.…”
Section: Mg-chelatase Has Three Componentsmentioning
confidence: 89%
“…The major impediment was the lack of an in itro assay, which was only achieved 6 years ago [2]. Since that time our knowledge of Mg-chelatase has expanded dramatically to the extent that the enzyme has been cloned and sequenced from several photosynthetic species [3][4][5][6][7][8][9][10].…”
Section: Scheme 2 Reaction Catalysed By Mg-chelatasementioning
confidence: 99%
See 3 more Smart Citations